O efeito do óleo-resina de copaíba sobre o desempenho e imunidade de frangos desafiados com escherichia coli patogênica - Guidotti, Micaela (2013)
The aim of this work was to evaluate the effect of oil-resin from the plant Copaifera sp. as phytogenic additive on broiler performance and as immunomodulatory agent. Five hundred broiler chicks were used (Cobb500 males), distributed in a randomized design experiment in factorial 5 x 2, composed of 10 treatments and five replications with 10 birds per pen. The treatments were divided in animals challenged and not challenged for all treatments: control group with and without challenge, oil-resin from copaiba 0.2%, group oilresin from copaiba 0.4%, group of oil-resin from copaiba 0.6 and group with growth promoter colistin. The challenge with pathogenic E. coli (4.5 x 109 UFCmL ) was realized at the age of four and 22 days old. The final weight, weight gain, feed intake and feed conversion were measured at weekly intervals until the age of 28 days. A in house indirect ELISA was standardized and immunoglobulin class IgA was evaluated. The cellular immunity was measured through skyn reaction test to phytohemagglutinin and analyzing the relative weight of the lymphoid organs. Performance data were analyzed through ANOVA and Turkey test with 5% of probability. For statistical evaluation of immunological data it was used multiple test non-parametric test, Kruskall-Wallis followed by T teste. The results showed that the inclusion of different levels of oil-resin from copaiba in broiler diet had similar performance when compared to the inclusion of antibiotic growth promoter. However it was observed an additive effect on antibody levels at the end of the trial period when oil-resin 0.2% was used.